2016
DOI: 10.1002/2016gl069786
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between assumed morphology and the direct radiative effect of light‐absorbing organic aerosol

Abstract: Mie theory is widely employed in aerosol top‐of‐the‐atmosphere direct radiative effect (DRE) calculations and to retrieve the absorptivity of light‐absorbing organic aerosol (OA) from measurements. However, when OA is internally mixed with black carbon, it may exhibit complex morphologies whose optical behavior is imperfectly predicted by Mie theory, introducing bias in the retrieved absorptivities. We performed numerical experiments and global radiative transfer modeling (RTM) to investigate the effect of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Challenges related to the definition of a chemical species in models add fundamentally to uncertainties in the refractive indices used as inputs to any optical model, particularly in the case of BC and organic carbon. The way the refractive indices of these species are retrieved can lead to large differences in their numerical values (Saleh et al, ). Stier et al () showed that the basic assumption regarding the refractive index of BC plays a key role in the calculation of radiative forcing.…”
Section: Impacts Of Aerosol Mixing State On Climate‐relevant Aerosol mentioning
confidence: 99%
“…Challenges related to the definition of a chemical species in models add fundamentally to uncertainties in the refractive indices used as inputs to any optical model, particularly in the case of BC and organic carbon. The way the refractive indices of these species are retrieved can lead to large differences in their numerical values (Saleh et al, ). Stier et al () showed that the basic assumption regarding the refractive index of BC plays a key role in the calculation of radiative forcing.…”
Section: Impacts Of Aerosol Mixing State On Climate‐relevant Aerosol mentioning
confidence: 99%
“…However, even if this was the case, our two-species (BC + brC) approach would still provide the optical parameters required for climate models to correctly represent the wavelength-dependent light absorption of HFO PM which we have observed; the inaccuracy would be in the relative attribution of absorption to the different light-absorbing species. Moreover, as demonstrated by Saleh et al (2016), climate models which employ Mie theory in radiative transfer calculations produce more accurate estimates of radiative forcing when Mie-theory-retrieved parameters are used, compared to more-complex retrievals.…”
Section: Introductionmentioning
confidence: 99%
“…Aerosols in the atmosphere affect the climate both directly by interacting with sunlight (i.e., absorption and scattering) and indirectly by altering cloud properties. The magnitude and even the sign of the impact of particle scattering and absorption, in particular, is not very well constrained, in part because they depend on many factors including particle size, shape, composition, and mixing state (Cazorla et al 2013;Laskin et al 2015;Fierce et al 2016;Saleh et al 2016). It is known that black carbon (BC) particles, for example, efficiently absorb solar radiation throughout the UV-visible region of the spectrum with an estimated anthropogenic contribution to positive radiative forcing second only to carbon dioxide (Bond et al 2013).…”
Section: Introductionmentioning
confidence: 99%